Antenatal care visits’ absenteeism at a secondary care medical facility in Southwest Nigeria. (2016)
Antenatal care (ANC) is a specialised pattern of care organized for pregnant women with the goal of maintaining good health and promoting safe delivery of healthy infants. It is an indispensable part of effective maternity care services. This study identified the factors responsible for absenteeism from ANC follow-up visits. It was a hospital-based prospective cross-sectional descriptive study conducted at a faith based secondary healthcare facility in Ibadan, Nigeria. Relevant data were retrieved using interviewer administered structured questionnaires and antenatal health record cards. The major reasons identified for absenteeism were delay in receiving hospital services due to long queues at service points and understaffing. The pregnant women aged 35 years and above were the most likely to miss the visits. Therefore, there is the need for hospital administrators and health care givers to make the services patient-friendly